2000
DOI: 10.1002/1097-0134(20001001)41:1<33::aid-prot60>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of cytosolic and mitochondrial glyoxalase II with acidic phospholipids in form of liposomes results in the inhibition of the cytosolic enzyme only

Abstract: Kinetics of cytosolic recombinant human glyoxalase II and bovine liver mitochondrial glyoxalase II were studied in the presence of liposomes made of different phospholipids (PLs). Neutral PLs such as egg phosphatidylcholine or dipalmitoylphosphatidylcholine did not affect the enzymatic activity of either enzymatic form. Liposomes made of dioleoyl phosphatidic acid or cardiolipin or phosphatidylserine also did not affect the enzymatic activity of mitochondrial glyoxalase II. Conversely, these negatively charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Applications include the study of virology, [1][2][3] ligand fishing, 4,5 bacteriology, 6-8 apoptosis, 9 cell biology and adhesion, 10,11 epitope mapping, [12][13][14] signal transduction, 15,16 immune regulation, 17 nucleic acid-nucleic acid interactions, [18][19][20] and nucleic acid-protein protein interactions, 21,22 and study of post-translational modifications. 23,24 Detection of proteins and nucleic acids is often performed using optical fluorescence based techniques, which are more costly and timely than electrical detection due to the need for expensive and bulky optical equipment and the process of fluorescent tagging. Thus, a robust label-free electrical detection technique can provide for a promising solution in lowering both reagent costs and instrumentation costs.…”
mentioning
confidence: 99%
“…Applications include the study of virology, [1][2][3] ligand fishing, 4,5 bacteriology, 6-8 apoptosis, 9 cell biology and adhesion, 10,11 epitope mapping, [12][13][14] signal transduction, 15,16 immune regulation, 17 nucleic acid-nucleic acid interactions, [18][19][20] and nucleic acid-protein protein interactions, 21,22 and study of post-translational modifications. 23,24 Detection of proteins and nucleic acids is often performed using optical fluorescence based techniques, which are more costly and timely than electrical detection due to the need for expensive and bulky optical equipment and the process of fluorescent tagging. Thus, a robust label-free electrical detection technique can provide for a promising solution in lowering both reagent costs and instrumentation costs.…”
mentioning
confidence: 99%
“…In plants and yeast both cytosolic and mitochondrial glyoxalase II play complementary roles in protection against the toxic effects of MG (6,14). It is possible that the mitochondrial enzyme hydrolyzes S-D-lactoylglutathione that has diffused or been transported into the mitochondrial matrix from the cytosol (12). It has also been suggested that uptake of S-D-lactoylglutathione is a possible pathway for the mitochondrial import of GSH (12), although direct import of GSH also occurs (32).…”
Section: Fig 3 Immunoblotting Of Glyoxalase Ii-luciferase Fusion Prmentioning
confidence: 99%
“…It is possible that the mitochondrial enzyme hydrolyzes S-D-lactoylglutathione that has diffused or been transported into the mitochondrial matrix from the cytosol (12). It has also been suggested that uptake of S-D-lactoylglutathione is a possible pathway for the mitochondrial import of GSH (12), although direct import of GSH also occurs (32). Alternatively mitochondrial glyoxalase II activity may be required to hydrolyze thiol esters of glutathione formed by non-enzymatic or enzymatic acyl transfer from mitochondrial thiol esters of coenzyme A (9).…”
Section: Fig 3 Immunoblotting Of Glyoxalase Ii-luciferase Fusion Prmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of label-free detection techniques have been proposed by researchers. Optical biosensors such as surface plasmon resonance, planar waveguides and resonant mirrors are adopted in a wide range of disciplines in the life sciences (Bernard and Lengeler 1978;Bier et al 1997;Jensen et al 1997;Hart et al 1999;Elliott et al 2000;Guermazi et al 2000;Jokiranta et al 2000;Scire et al 2000;Steinrucke et al 2000;Uegaki et al 2000;Xing et al 2000;Wilson 2002). Microcantilever biosensors are reported as a label-free detection technique.…”
Section: Introductionmentioning
confidence: 99%